THE SIGNIFICANCE OF PATHOLOGY IN NURSING PRACTICE - Sadulloeva Mashkhura Adizovna; Rajabova Rokhila Bakhshullovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Pathology, the study of diseases and their processes, holds critical importance in the field of nursing. For nursing professionals, a solid understanding of pathology enhances patient assessment, aids in the identification of disease processes, and informs the provision of evidence-based care. This article explores the relevance of pathology in nursing education and practice, emphasizing its role in improving patient outcomes.